Membaca Lakon Ardini Pangastuti Menanamkan dan Menghidupkan Wayang pada Generasi Muda (Sutasoma : Jurnal Sastra Jawa, 2022)
This research discusses how the Javanese novelist, Ardini Pangastuti, uses her work Lakon to inculcate and reinvigorate wayang in the young generation. In this work, the pragmatic perspective is applied based on linguistic concepts. The pragmatic point of view assumes that the language (form of speech, literary work) is an expression that suggests the speaker's intentions and the context of the speech. Meanwhile, qualitative data analysis was carried out utilizing interpretation-interactive and inductive methods. All of the results are provided in a verbal-descriptive style. The following are the study's findings. First, Lakon expresses a strong deliberate interaction (intention) between the author and the novel's characters in instilling and reviving wayang to the young generation. Second, the Lakon novel does not transform wayang characters into characters so that the novel tends to be reportative due to the dominant description of wayang stories obtained from observations and interviews. Third, the author and novel's characters succeeded in instilling and reviving wayang in the young generation through the narrative structure by combining traditional concepts with modern tools, includding technical innovations in performances, communicative language, and wayang performing management, despite the fact that these methods are common in the context of wayang development. Keywords: a novel; wayang; Ardini Pangastuti; pragmatic; young generation